ANALISIS DAN DESAIN SISTEM INFORMASI KOPERASI WANITA SETIA BHAKTI WANITA PADA UNIT SIMPAN PINJAM - Marsha Sevin Aldilla; Teguh Sutanto; Erwin Sutomo (Jurnal Sistem Informasi Universitas Dinamika, 2015)
Koperasi Wanita Setia Bhakti Wanita are credit unions that adopts a joint responsibility. For handling system, currently the cooperative already has a desktop-based information systems. But the cooperative plans to reengineering of information systems. Reengineering should be held because the current system is not integrated with either, so it must be done continuously updates the system.In this study the authors analyze the current system, is also making a new information system for the cooperative. Analysis of these development starts from observation, interviews, and the collection of documents, in order to get the analysis of the system which consist of documents Business Diagram, Activity Diagram, and the Business Entity. After doing analysis system followed by designing a system. Design system generates a document Use Case Diagram, Use Case Description, Sequence Diagram, Class Diagram, Component Diagram, and Deployment diagrams. Last documents have been produced, conducted a search to examine the relationship between documents.The Results from this study which include systems analysis, namely the outcome of the current cooperative system documentation. Developing a system is the result from development analysis system. And the last form of the design of the website interface development system created.